Cover Cropping in a sloping, non-irrigated vineyard: I - effects on weed composition and dynamics - Monteiro,A. (2008)
The influence of two sward treatments and soil cultivation on the composition, the structure, and the evolution of the biomass of vineyard weed communities was examined. The 3-year study (2002-2004) was carried out in a sloping, non-irrigated vineyard, cv. Cabernet Sauvignon, in the Estremadura winegrowing region of Portugal. The experimental treatments were: soil tillage (control); permanent sown cover crop - Lolium perenne Nui, L. multiflorum Bartíssimo, Festuca ovina Ridu, F. rubra ssp. rubra Echo, Trifolium incarnatum. Red, T. repens Huie and T. subterraneum Claire; and permanent resident vegetation. Total weed biomass in the spring did not reveal significant differences between treatments, but varied annually. The management practices - e.g. time and number of soil cultivations and inter-row mowing - were determinant in weed biomass evolution. Canonical correspondence analysis revealed significant treatment effects on community structure. Three years after the experiment was set up, in the soil tillage treatment weed composition was dominated by annual broad-leaved species, namely five Geraniaceae species, Medicago polymorpha and Sonchus oleraceus. The perennial broad-leaved species Oxalis pes-caprae was also a dominant species in soil tillage. In both sward treatments there was an increase in the perennial broad-leaved and grass species. Compared to soil tillage, in the resident vegetation treatment there was a significant increase in perennial species, such as Rumex crispus, Veronica anagallis-aquatica and Polypogon monspeliensis, and in the annuals Melilotus indica and Avena sterilis. The increase in these perennial species, which are considered to compete with vines, requires more frequent mowing in the summer. In the permanent sown cover crop treatment, L. perenne and T. repens displayed the ability to re-establish successfully, and their abundance decreased or suppressed most of the annual and perennial weed species.